Beyond Quality in Early Childhood Education and Care - Gunilla Dahlbeg; Moss Peter; Pence Alan (Routledge - Taylor & Francis Group, 2007)
The book challenges many of the basic assumptions and assertions of mainstream early childhood policy and practice, showing that there are other possibilities - and therefore choices to be made. Preface, Acknowledgements, What This Book is about, Theoretical Persectives: Modernity and Postmodernity and Power and Ethics, Constructing Early Childhood: What Do We Think It Is?, Constructing the Early Childhood Institution: What Do We Think They Are For?, Beyond the Discourse of Quality to the Discourse of Meaning Making, The Stockholm Project: Constructing a Pedagogy that Speaks in the Voice of the Child and the Pedagogue and the Parent, Pedagogical Documentation: A Practice for Reflection and Democracy, Minority Directions in the Majority World: Threats and Possibilities, References, Index.